2017
DOI: 10.1177/0004867417714337
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of changing psychological outcomes following the Victorian Black Saturday bushfires

Abstract: Although rates of mental health problems diminished over time, they remained higher than national levels. Findings suggest that policy-makers need to recognize that the mental health consequences of disasters can persist for many years after the event and need to allocate resources towards those who are most at risk as a result of substantive losses and ongoing life stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 43 publications
3
88
1
4
Order By: Relevance
“…In a longitudinal cohort of adults in Australia, it has been demonstrated that other life stressors are important modifiers of the relationship between fire exposure and psychopathology, with those who have more stressors being both less likely to recover if they have major depression or PTSD early following a wildfire, and more likely to develop late symptoms if not present early on [65]. This, again, argues that much of the mental health effects related to wildfires may be mediated by stress rather than due to a specific toxicant exposure.…”
Section: Health Effects Of Other Aspects Of Wildfire Disastersmentioning
confidence: 99%
“…In a longitudinal cohort of adults in Australia, it has been demonstrated that other life stressors are important modifiers of the relationship between fire exposure and psychopathology, with those who have more stressors being both less likely to recover if they have major depression or PTSD early following a wildfire, and more likely to develop late symptoms if not present early on [65]. This, again, argues that much of the mental health effects related to wildfires may be mediated by stress rather than due to a specific toxicant exposure.…”
Section: Health Effects Of Other Aspects Of Wildfire Disastersmentioning
confidence: 99%
“…The size and severity of the event often undermines the capacity of systems and services to respond, resulting in significant loss of infrastructure and facilities. The subsequent ongoing stressors and social disruption add to the trauma of the original event and can reduce mental health and well‐being for years afterward (Bonanno, Brewin, Kaniasty, & La Greca, ; Bryant et al., ; Bryant et al., ). In addition to the direct threats of the disaster experienced by adults, children can experience specific challenges associated with different stages of physical, mental, emotional, cognitive, and social stages of development (Anderson, ; Bonanno et al., ; Peek, ).…”
mentioning
confidence: 99%
“…Contamination of drinking water supplies and shortages were common in many bushfire-affected areas (Lal 2020). For rural communities in affected areas, whose resilience was already affected by the ongoing drought (Austin et al 2018) or the experience of previous major bushfires (Bryant et al 2018), the 2019-20 bushfires imposed significant mental burdens. The required service mix changed as a result of the fires, with more people requiring mental health services (Public Health Association of Australia 2020).…”
Section: Service Deliverymentioning
confidence: 99%